Insomnia, worry, anxiety and depression as predictors of the occurrence and persistence of paranoid thinking. - Freeman, D; Stahl, D; McManus, S; Meltzer, H; Brugha, T; Wiles, N; Bebbington, P (2012)
PURPOSE: Our theoretical model proposes that insomnia, worry, and negative affect are important determinants of paranoid thinking. Anxiety produces anticipation of threat, depression increases the sense of vulnerability, worry leads to implausible ideas, and insomnia exacerbates negative affect and creates an altered perceptual state. The study objective was to examine for the first time these factors as predictors of the onset of new paranoid thinking and of the persistence of existing paranoid thinking. METHOD: A total of 2,382 participants in the 2000 British National Psychiatric Morbidity Survey were followed-up 18 months after their first assessment. Baseline assessments were used to predict the development and persistence of paranoid thinking at follow-up. Data were weighted to be representative of the general household population. RESULTS: Insomnia, worry, anxiety, depression and depressive ideas were each substantial predictors both of new inceptions of paranoia and of the persistence of existing paranoid thinking. Worry and insomnia were the strongest predictors. For example, insomnia at the first assessment led to a more than threefold increase in later inceptions of paranoid thinking. CONCLUSIONS: The study indicates that insomnia, worry, anxiety and depression are potential risk factors for new inceptions of paranoid thinking. The results also corroborate an emerging literature indicating that anxiety, worry and depression may encourage the persistence of paranoid thinking. The study provides the first longitudinal evidence linking insomnia and paranoia. The important clinical implication is that the use of interventions for common mental health difficulties in people with psychosis may have the additional benefit of reducing paranoia.